Based on Gene Expression Analysis: Low-Density Neutrophil Expression Is a Characteristic of the Fast Responders Treated With Guselkumab for Psoriasis - Lu, Jiajing; Wang, Yu; Li, Ying; Zhong, Xiaoyuan; Gong, Yu; Ding, Yangfeng; Yu, Ning; Shi, Yuling (Frontiers in Immunology, 2022)
Psoriasis is a common chronic inflammatory skin disease individuals worldwide. The therapeutic course for the disease is generally designed upon the severity of the disease. In this study, RNA-seq was performed on the skin lesions of 37 patients with psoriasis treated with guselkumab before and after treatment, and the patients were divided into fast responder and slow responder according to PASI score to analyze the differentially expressed genes (DEGs) between them. Moreover, Gene Ontology (GO) analysis, Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis and Gene Set Enrichment Analysis (GSEA) were performed to explore biological mechanisms in psoriasis. And then, a protein-protein interaction network was constructed and GSVA was used to analysis the 17 DEGs, including IL-1β, CXCL8, S100A12 and MMP9. GO and KEGG analysis of target genes found that DEGs were primarily associated with immune response, neutrophil activation, neutrophil degranulation. GESA reminder fast responders was mainly involved in low-density neutrophils and abundant NK cells. And the GSVA shows that the DEGs were down-regulated after the early stage of the fast responder and the reverse in the slow responder by GSVA analysis. In a word, these findings indicated that these DEGs may be used as potential diagnostic and predictive biomarkers for psoriasis who was be treated by guselkumab.